A mobilização dos registros de representação semiótica na prática pedagógica do processo de ensino-aprendizagem dos números racionais - Proença, Laís Isabele (Universidade Federal de São Carlos, 2021)
This research aimed to analyze how teaching practice interferes in the process of acquisition and articulation of different semiotic registers of rational numbers, in which the guiding question is presented How the pedagogical practice in the process of mathematical literacy, in the teaching of rational numbers, does it contribute to the mobilization of semiotic representation records?. In addition, I present the justification for the choice of the topic, in which I have been working for more than seven years only in public schools in the region of my city of Itaporanga-SP, I wonder why many students do not make connections of different representations of the same mathematical object. , mainly related to rational numbers. It also exposes the theoretical foundation of the research, as well as the methodology for its development, in which, for the development of the didactic sequences, it sought to use as theoretical support Duval's Theory of Semiotics Records. The research is qualitative in nature, in which a didactic sequence was applied with the participation of 14 6th grade students, in which the classes took place synchronously for those who had access to the internet and asynchronously through a group of WhatsApp in the room with videos of classes. Understanding that the teaching of rational numbers is a challenge for the mathematics teacher, based on the premises that the Theory of Records of Semiotic Representation brings us, we started to have a more critical, reflective and articulated look at how we should have our methodology in the classroom and critically analyze the teaching materials that are available for us to use, as these are the bases for our work. However, with this research, it is concluded that it is not only the materials that must be in accordance with the objective of mobilizing the different registers of semiotic representation of rational numbers, it is necessary that both the materials and our pedagogical practice are favorable in order to achieve the skills to be developed by our students.
The mobilization of semiotic representation records in the pedagogical practice of the teaching-learning process of rational numbers
Keywords: Letramento matemático; Ensino Fundamental; Números racionais; Semiótica; Mathematical literacy; Elementary School; Rational numbers; Semiotics; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM